The changing art of seduction. - Barendregt, Bart A. 1968- (SPAFA Journal : a publication of the SEAMEO Regional Centre for Archaelogy and Fine Arts)
Bart Barendregt reflects on ritual courtship, performing prostitutes, and erotic entertainment.